Lithium ion battery

By adjusting the opening volume of silicon carbon material and the mass proportion of compound A, combined with the use of high tensile strength negative electrode current collector and fluorovinyl carbonate, the thermal safety and circulation of lithium-ion batteries during fast charging are solved. Lifetime issues achieve more efficient battery performance and safety.

CN119181856APending Publication Date: 2024-12-24ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411602049.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Lithium-ion batteries have thermal safety and cycle life problems during fast charging, especially due to the breakage of negative current collector and lithium dendrites caused by volume expansion of silicon-carbon materials, which increases the risk of thermal runaway in the battery.

Method used

By adjusting the pore volume of silicon carbon material and the mass proportion of compound A, combined with the use of high tensile strength negative electrode current collector and fluorovinyl carbonate, a linear recessed area is further provided in the negative electrode active material layer and the electrolyte is in the electrolyte solution Compound B is added to improve the thermal safety performance and cycle life of the battery.

Benefits of technology

It effectively improves the fast charging performance and thermal safety performance of the battery, reduces the stress caused by negative electrode expansion, inhibits the generation of lithium dendrites, and improves the cycle life and thermal safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181856A_ABST
    Figure CN119181856A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and provides a lithium ion battery. A negative plate of the battery comprises a negative current collector and a negative active material layer arranged on at least one side surface of the negative current collector, the negative active material layer comprises a negative active material, and the negative active material comprises a silicon carbon material; the open pore volume of the silicon carbon material is recorded as x mm < 3 > / g; the electrolyte comprises a compound A, and based on the total mass of the electrolyte, the mass ratio of the compound A is recorded as y%; the chemical formula of the compound A is shown as a formula I and / or a formula II; x and y meet the condition that y / x is more than 0.05 and less than or equal to 120, the fast charging performance of the battery can be improved, the thermal safety performance of the battery is improved, and the cycle life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery. Background Art

[0002] As the world pursues the goal of carbon neutrality, green travel and renewable energy have become important issues of the times. As an efficient, environmentally friendly and renewable energy storage device, lithium-ion batteries are gradually becoming a core component in this transformation. The popularity of electric vehicles, electric bicycles and energy storage equipment cannot be separated from the support of lithium-ion batteries. However, with the continuous expansion of application areas and the rapid expansion of market scale, the fast charging technology and safety of lithium-ion batteries have become the focus of industry attention. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a lithium-ion battery. By adjusting the open pore volume of the silicon-carbon material and the mass ratio of compound A to meet a specific relationship, the battery's fast charging performance and cycle performance can be improved, and the battery's hot box safety performance can be improved.

[0004] In order to achieve the above object, the present invention provides a lithium ion battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0005] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector. The negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon material. The open pore volume of the silicon-carbon material is recorded as x mm 3 / g; x satisfies: 0.1≤x≤100;

[0006] The electrolyte includes compound A, and the mass proportion of compound A is y% based on the total mass of the electrolyte; the chemical formula of compound A is shown in formula I and / or formula II:

[0007] Formula I: Formula II: Wherein, R1, R2, R3, and R4 independently include F, Cl-substituted or unsubstituted hydrocarbon groups or hydrocarbonoxy groups having 1 to 8 carbon atoms, at least one of R1 and R2 contains F, and at least one of R3 and R4 contains F;

[0008] x and y satisfy: 0.05<y / x≤120.

[0009] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0010] (1) The lithium-ion battery provided by the present invention can improve the fast charging performance of the battery, and increase the thermal safety performance and cycle life of the battery by adjusting the open pore volume of the silicon-carbon material and the mass proportion of the compound A to meet a specific relationship;

[0011] (2) The lithium-ion battery provided by the present invention can suppress the rupture of the negative electrode current collector caused by the expansion of the negative electrode, and further improve the thermal safety performance of the battery by further adjusting the mass ratio of the fluoroethylene carbonate in the electrolyte, the mass ratio of the silicon element in the negative electrode active material, and the tensile strength of the negative electrode current collector to meet a specific relationship.

[0012] (3) The lithium-ion battery provided by the present invention further provides a linear depression region on the negative electrode active material layer. When the width of the linear depression region is adjusted within a specific range, the stress caused by the volume expansion of the silicon-containing negative electrode material can be dispersed, thereby improving the cycle life of the battery;

[0013] (4) The lithium-ion battery provided by the present invention, when compound B is further added to the electrolyte and the mass proportion of compound B is adjusted to a specific range, can inhibit the formation of lithium dendrites, reduce the risk of thermal runaway of the battery, and improve the cycle life of the battery.

[0014] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 FIG. 1 is a schematic diagram showing the structure of a negative electrode active material layer in an example of the present invention.

[0016] Figure numerals: 1, linear depressed area; 2, pit; 3, negative electrode active material layer. DETAILED DESCRIPTION

[0017] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0018] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0019] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0020] In the present invention, the term "open pore volume" refers to the volume of pores in the internal pore structure of the silicon-carbon material that are connected to the outside world, excluding the volume of closed pores.

[0021] In the present invention, the term "hydrocarbon group" refers to a group formed by replacing the hydrogen atom in a hydrocarbon with other groups (such as an alkyl group, a halogen atom, a hydroxyl group, a nitro group, etc.).

[0022] In the present invention, the term "hydrocarbyloxy group", also known as "alkoxy group", refers to a group formed by connecting a hydrocarbon group to an oxygen atom.

[0023] The present invention provides a lithium ion battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0024] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector. The negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon material. The open pore volume of the silicon-carbon material is recorded as x mm 3 / g; x satisfies: 0.1≤x≤100;

[0025] The electrolyte includes compound A, and the mass proportion of compound A is y% based on the total mass of the electrolyte; the chemical formula of compound A is shown in formula I and / or formula II:

[0026] Formula I: Formula II: Wherein, R1, R2, R3, and R4 are independently F-, Cl-substituted or unsubstituted hydrocarbon groups or hydrocarbon oxy groups having 1 to 8 carbon atoms, preferably hydrocarbon groups or hydrocarbon oxy groups having 4 or 6 carbon atoms, at least one of R1 and R2 contains F, and at least one of R3 and R4 contains F;

[0027] x and y satisfy: 0.05<y / x≤120.

[0028] Exemplarily, the value of y / x can be 0.055, 0.06, 0.07, 0.08, 0.09, 0.1, 0.5, 1, 5, 10, 20, 40, 60, 80, 100, 110, 115, 116, 117, 118, 119, 120 or any point value in the range consisting of any two of the above point values.

[0029] Exemplarily, the open pore volume x of the silicon-carbon material satisfies: 0.1≤x≤100; the open pore volume of the silicon-carbon material may be, for example, 0.1 mm 3 / g, 0.3mm 3 / g, 0.5mm 3 / g, 1mm 3 / g, 5mm 3 / g, 10mm 3 / g, 20mm 3 / g, 30mm 3 / g, 40mm 3 / g, 50mm 3 / g, 60mm 3 / g, 70mm 3 / g, 80mm 3 / g, 90mm 3 / g, 95mm 3 / g, 100mm 3 / g or any point value in the range consisting of any two of the above point values, preferably 1≤x≤70.

[0030] Illustratively, the hydrocarbon group with 1-8 carbon atoms includes, but is not limited to, an alkyl group with 1-8 carbon atoms, an alkenyl group with 1-8 carbon atoms, and an alkynyl group with 1-8 carbon atoms and 1-6 carbon atoms; the hydrocarbonoxy group with 1-8 carbon atoms includes, but is not limited to, an alcoholic hydroxyl group with 1-8 carbon atoms, an ether group with 1-8 carbon atoms, an aldehyde group with 1-8 carbon atoms, and a keto group with 1-8 carbon atoms.

[0031] Silicon-carbon materials will undergo significant volume expansion during the battery charging and discharging process, which will not only cause cracks in the structure of the negative electrode active material and affect the rapid transmission of lithium ions, but will also intensify the side reactions between the negative electrode active material and the electrolyte, generating more water and acid products, further intensifying the side reactions and making the battery more susceptible to thermal runaway or explosion risks.

[0032] The silicon-carbon material in the present invention has an open-pore structure and a certain range of open-pore volume, which can buffer the volume expansion of the silicon-carbon material during the charging and discharging process, reduce the structural damage of the negative electrode material caused by the volume change, reduce the occurrence of side reactions, improve the safety performance of the battery, and provide more lithium storage sites, the diffusion resistance of lithium ions inside the negative electrode material is smaller, and the rate of lithium ion extraction and insertion in the negative electrode of the battery is higher, which can improve the charging and discharging efficiency and fast charging performance of the battery. Compound A is added to the electrolyte, and compound A is a cyclic carbonate and / or a linear carboxylate, with low viscosity and high fluidity. Compound A can be well filled in the open-pore structure of the silicon-carbon material, and the rate of lithium ion embedding into the silicon-carbon material is increased. The protective film formed by compound A on the surface of the negative electrode can extend to the inside of the open-pore structure of the silicon-carbon material, which can fully inhibit the expansion of the silicon-carbon material and reduce the expansion of the negative electrode; on the other hand, it can isolate the acid, moisture, oxygen and other substances generated by the side reactions in the battery, reduce the rapid accumulation of heat caused by the side reactions of the silicon-carbon material and other substances in the negative electrode, and compound A can timely export the heat generated by the negative electrode through its large fluidity, thereby improving the thermal safety performance of the battery.

[0033] The synergy between silicon-carbon material and compound A can effectively improve the fast charging performance and cycle life of the battery and enhance the safety performance of the battery.

[0034] In some embodiments, x and y satisfy: 0.1<y / x≤100. When x and y further satisfy the above range, the synergistic effect between the open pore volume of the silicon-carbon material and the compound A can be further enhanced, the fast charging performance of the battery can be further improved, and the hot box safety performance of the battery can be improved.

[0035] In some embodiments, when the open pore volume of the silicon-carbon material is adjusted to meet 0.1≤x≤100, it is possible to avoid the situation where the open pore volume of the silicon-carbon material is too large when x>100, making the negative electrode of the battery more susceptible to external environmental factors such as moisture and oxygen. These environmental factors will aggravate the degree of side reactions, produce harmful substances or gases, and affect the safety performance of the battery. Moreover, when the open pore volume of the silicon-carbon material is within the above range, it can alleviate the volume change of silicon particles during the charging and discharging process, reduce the structural damage of the negative electrode material caused by the volume change, and reduce the phenomenon of material pulverization and peeling, thereby further improving the cycle life of the battery.

[0036] Exemplarily, the open pore volume of the silicon-carbon material can be determined using a low-temperature nitrogen adsorption method, which specifically includes the following steps: crush the silicon-carbon material into powder, add a sample of about 1 g in weight into a sample tube, weigh the weight of the sample and the sample tube, recorded as m1; place the sample tube in a degassing station for degassing, and after the degassing is completed, weigh the mass of the sample tube to obtain the mass of the degassed sample, recorded as m2; use a Tri Star II specific surface area analyzer for testing, input the measured sample mass data (m1, m2), start the instrument to measure the sample, and the analyzer will automatically perform isothermal adsorption and desorption analysis, and calculate the specific surface area and open pore volume of the silicon-carbon material by measuring the amount of nitrogen adsorbed on the sample surface.

[0037] In some embodiments, the mass proportion y of the compound A satisfies: 5≤y≤30, and the mass proportion of compound A can be, for example, 5%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30% or any point value in the range consisting of any two of the above point values. Further adjusting the mass proportion of compound A to meet the above range can avoid the situation when y is less than 5, the content of compound A in the electrolyte is too little, the viscosity of the electrolyte is high and the impedance is high, the migration rate of lithium ions in the electrolyte is low, and the film formation of compound A on the surface of the negative electrode is insufficient, the interface film structure is unstable, and the side reactions of the negative electrode cannot be fully prevented, resulting in rapid accumulation of heat and generation of more gas, which in turn leads to safety problems such as thermal runaway or explosion of the battery; avoid the situation when y is greater than 30, the content of compound A in the electrolyte is too high, the proportion of other effective ingredients is reduced, which is not conducive to the transmission and storage of lithium ions in the electrolyte, resulting in a reduction in the capacity of the battery; it is also easy to cause the formation of an excessively thick SEI film on the electrode surface, increase the interface impedance, hinder the migration of lithium ions, and deteriorate the charge and discharge performance of the battery at a high rate; thereby adjusting the mass proportion of compound A to meet the above range to improve the charge and discharge efficiency of the battery and improve the hot box safety performance of the battery.

[0038] In some embodiments, compound A shown in formula I includes at least one of the following compounds:

[0039]

[0040]

[0041] In some embodiments, the compound A shown in Formula II includes at least one of the following compounds:

[0042]

[0043] In some embodiments, the compound A includes a compound represented by formula I and a compound represented by formula II, and the mass ratio of the two is 1:(1-4), for example, it can be 1:1, 1:2, 1:3, 1:4 or any point value in the range composed of the above two point values.

[0044] When the mass ratio of the compound represented by Formula I and the compound represented by Formula II is further adjusted to meet the above range, the compound A represented by Formula II has a higher electrochemical window, which can improve the stability of the electrolyte at high voltage, and the compound A represented by Formula I is relatively easier to form a film on the electrode surface to protect the electrode. The combination of the two can further improve the high voltage resistance of the battery, improve the thermal safety of the battery, and also improve the battery charging and discharging efficiency and cycle life.

[0045] In some preferred embodiments, compound A is a combination of I-2 and II-1. The present invention has found through a large number of experimental studies that when compound A is a combination of I-2 and II-1, and the mass ratio of the two is in the range of 1: (1-4), the role of compound A can be better exerted, and the fast charging performance and safety performance of the battery can be further improved.

[0046] In some embodiments, the sphericity of the silicon-carbon material is 0.5-1, and the sphericity of the silicon-carbon material can be, for example, 0.5, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.86, 0.88, 0.90, 0.92, 0.94, 0.96, 0.98, 0.99, 0.999, 1 or any point value in the range of the above two point values. The sphericity of the silicon-carbon negative electrode material can affect the flatness and burrs of the surface of the negative electrode sheet. Further adjusting the sphericity of the silicon-carbon material to meet the above range can promote the uniform deposition of lithium ions at the negative electrode and improve the fast charging performance and safety performance of the battery.

[0047] Exemplarily, the testing method for sphericity Q may include the following steps: analyzing the image of each particle in the SEM photograph of the composite material at a certain magnification (for example, 2500 times) through image processing software (such as Image ProPlus) to obtain the circumference and area of ​​each particle, and respectively calculating the circumference equivalent radius r1 and area equivalent radius r2 of each particle, then the sphericity S of each particle = r2 / r1, and then performing quantitative weighted averaging of the sphericity of each particle to obtain the average sphericity of the silicon-carbon material composite material.

[0048] In some embodiments, the Dv10 of the silicon-carbon material is 1 μm-10 μm, and the Dv10 of the silicon-carbon material can be, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any point value in the range of the above two point values, preferably 1 μm-8 μm. When the Dv10 of the silicon-carbon material is further adjusted to meet the above range, the specific surface area of ​​the silicon-carbon material can be further optimized, and the effective reaction interface of the silicon-carbon material can be increased, which is beneficial to improving the energy density and cycle life of the battery; improving the electrode structure, improving the transmission efficiency of lithium ions, further improving the charge and discharge efficiency of the battery, and enhancing the fast charging performance of the battery.

[0049] In some embodiments, the silicon-carbon material is doped with element M, and element M includes at least one of K, Ca, and Na. Preferably, the content of element M is 100ppm-10000ppm, and the content of element M can be, for example, 100ppm, 200ppm, 300ppm, 500ppm, 1000ppm, 2000ppm, 4000ppm, 6000ppm, 8000ppm, 10000ppm, or any point value in the range composed of the above two point values. When the content of the doped element of the silicon-carbon material is further adjusted to meet the above range, the electronic conductivity of the positive electrode active material can be improved, the lithium ion transmission efficiency between the negative electrode active material particles can be increased, and the material structure can be stabilized, the formation of lattice defects can be reduced, the internal resistance of the silicon-carbon material can be reduced, the heat generation can be reduced, and the thermal safety performance of the battery can be improved.

[0050] Exemplarily, the test method for the content of doping elements in the silicon-carbon material can be measured by EDS (Energy Dispersive X-ray Spectroscopy) test; and / or by ICP (Inductively Coupled Plasma) test.

[0051] The present invention has found that the silicon-carbon material has a certain open pore volume, which can alleviate the volume change of silicon particles during the charge and discharge process to a certain extent, and reduce the material structure damage caused by the volume change; but the excessive open pore volume of the silicon-carbon material will aggravate the degree of negative electrode side reactions and affect the safety performance of the battery. Therefore, the effect of only adjusting the open pore volume of the silicon-carbon material to alleviate the volume expansion of the negative electrode is limited. Moreover, as the silicon content in the negative electrode material increases, the volume expansion of the negative electrode material will produce greater stress on the negative electrode current collector, causing the negative electrode current collector to break, which is likely to increase the risk of thermal runaway of the battery. Therefore, in order to further alleviate the volume expansion of the negative electrode material, the present invention further proposes:

[0052] In some embodiments, the tensile strength of the negative electrode current collector is recorded as σMPa; σ satisfies: 450≤σ≤750, and the tensile strength of the negative electrode current collector can be, for example, 450MPa, 475MPa, 500MPa, 525MPa, 550MPa, 575MPa, 600MPa, 625MPa, 650MPa, 675MPa, 700MPa, 725MPa, 750MPa or any point value in the range of the above two point values. The tensile strength of conventional negative electrode current collectors in the art is 300MPa-450MPa, and the present invention uses a negative electrode current collector with high tensile strength.

[0053] On the basis that x and y satisfy 0.05<y / x≤120, the present invention further selects a negative electrode current collector whose tensile strength satisfies the above range, which can better withstand the mechanical stress generated by the volume expansion of the negative electrode material during the battery charging and discharging process, and reduce the battery thermal runaway caused by deformation or fracture of the negative electrode current collector. Moreover, when the negative electrode current collector with high tensile strength faces the stress generated by the volume change during the charging and discharging of the electrode material, it can make the stress distribution more uniform, reduce the stress concentration in the contact area between the electrode and the negative electrode current collector, avoid the adhesion failure and peeling of the negative electrode active material caused by stress concentration, and can further improve the cycle life of the battery.

[0054] In some embodiments, the negative electrode current collector with high tensile strength used in the present invention is a high-strength copper foil, or a coating that improves tensile strength is applied to the surface of the copper foil. Exemplarily, the coating includes but is not limited to one or more of Cr2O3, graphite, and polyimide coatings.

[0055] In some embodiments, the thickness of the negative electrode current collector is 2 μm-10 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any point value in the range of two points above, preferably 3 μm-8 μm. Further adjusting the thickness of the negative electrode current collector to meet the above range helps to reduce the electrode thickness, thereby reducing the overall volume and weight of the battery and improving the energy density of the battery.

[0056] Exemplarily, the test method for the tensile strength of the negative electrode current collector specifically includes the following steps: cutting the current collector into strips of 15 mm ± 0.2 mm; using a WD-D3 electronic universal testing machine with a gap of 50 mm between the upper and lower clamps, clamping the two ends of the current collector with the clamps, starting the test at a speed of 100 mm / min until the test stops, and recording the tensile strength (fracture strength) σ; taking the average value of three tests with an error of no more than 10%, which is the tensile strength of the negative electrode current collector.

[0057] As the silicon content in the negative electrode material increases, the expansion problem becomes more significant, which not only generates greater stress on the current collector, causing the risk of thermal runaway of the battery, but also causes the SEI film on the electrode surface to rupture, resulting in the continuous consumption of electrolyte to form a new SEI film, and because the electrolyte is in direct contact with the negative electrode, side reactions continue to occur between the negative electrode material and the electrolyte, causing the battery capacity to drop rapidly. In order to further reduce electrolyte side reactions, optimize the cycle performance of the battery and improve the thermal safety of the battery, the present invention further proposes:

[0058] In some embodiments, the content of silicon in the negative electrode active material is recorded as m%; the electrolyte includes fluoroethylene carbonate, and the mass proportion of fluoroethylene carbonate based on the total mass of the electrolyte is recorded as n%; m, n and σ satisfy: 10<(n+σ) / m≤500. Exemplarily, the value of (n+σ) / m can be, for example, 10.1, 10.5, 11, 13, 15, 20, 50, 100, 150, 200, 250, 300, 350, 400, 450, 470, 490, 495, 500 or any point value in the range of the above two point values. The fluoroethylene carbonate in the electrolyte can form an effective solid electrolyte interface film (SEI film) on the electrode surface, reducing the rapid decrease in battery capacity caused by side reactions. Further adjust m, n and σ to satisfy the above relationship. The higher the silicon content m, the higher the volume expansion of the negative electrode. The content n of fluoroethylene carbonate and the tensile strength σ of the negative electrode current collector also need to increase accordingly, that is, n+σ increases, so as to alleviate the problems of electrolyte side reactions caused by the increased expansion of the negative electrode and battery corner cracks caused by stress on the current collector. Therefore, fluoroethylene carbonate and the tensile strength of the negative electrode current collector work together to further improve the thermal safety problems caused by the volume expansion of the silicon negative electrode and increase the cycle life of the battery.

[0059] In some embodiments, the content ratio m of the silicon element satisfies: 1<m≤50, and the content ratio of the silicon element can be, for example, 1.001%, 1.01%, 1.05%, 1.1%, 1.5%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 46%, 47%, 48%, 49%, 50% or any point value in the range composed of the above two point values. Further adjusting the content ratio of the silicon element to meet the above range can avoid that when m>50, the content of the silicon element is too high, and the volume change of the silicon-containing negative electrode material during the charge and discharge process is more significant, resulting in the crushing of the negative electrode material particles, the separation of the negative electrode active material and the current collector, and the formation of an unstable solid electrolyte interphase (SEI) film. The rupture of the SEI film will lead to the continuous consumption of the electrolyte, thereby greatly affecting the cycle stability and performance of the battery.

[0060] For example, the content of silicon in the negative electrode active material can be tested by thermogravimetric analysis, for example, using a Shimadzu DTG-60 thermogravimetric analyzer, specifically comprising the following steps: taking a sample of 5 mg, using air as the atmosphere, heating from room temperature to 900°C at a rate of 10°C / min and keeping the temperature constant for 40 minutes, and measuring the final weight residual percentage N after the entire test. The relationship between the content H of silicon and N is: H=7N / 15.

[0061] In some embodiments, the mass proportion n of fluoroethylene carbonate satisfies: 0<n≤20, and the mass proportion of fluoroethylene carbonate can be, for example, 0.001%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 16%, 17%, 18%, 19%, 20% or any point value in the range composed of any two of the above point values. Further adjusting the mass proportion of fluoroethylene carbonate to meet the above range can avoid excessive fluoroethylene carbonate content in the electrolyte when n>20, resulting in too thick SEI film, hindering the migration of lithium ions, and causing the battery fast charging performance to decrease; and avoid excessive fluoroethylene carbonate decomposition to produce gas and release heat, resulting in increased internal pressure of the battery, thermal runaway and other risks.

[0062] In order to further disperse the stress caused by the volume expansion of the silicon-containing negative electrode material and improve the cycle life of the battery, in some embodiments, a linear depression is provided on the negative electrode active material layer, and the width of the linear depression is 50μm-200μm. The width of the linear depression can be, for example, 50μm, 75μm, 100μm, 125μm, 150μm, 175μm, 200μm or any point value in the range of two points above. Further adjusting the width of the linear depression on the negative electrode active material layer to meet the above range not only reserves space for the expansion of the negative electrode, reduces the pressure on the negative electrode current collector, but also increases the contact area between the negative electrode material and the electrolyte, increases the lithium ion transmission efficiency, and increases the battery's liquid retention, thereby improving the battery's cycle performance.

[0063] In some embodiments, the depth of the linear depression area is 3μm-45μm. The depth of the linear depression area can be, for example, 3μm, 5μm, 8μm, 9μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 26μm, 28μm, 30μm, 32μm, 34μm, 36μm, 38μm, 40μm, 42μm, 44μm, 45μm or any point value in the range composed of any two of the above point values. Further adjusting the depth of the linear depression area to meet the above range can optimize the transmission path of lithium ions, reduce the local current density on the negative electrode surface, and reduce polarization, thereby improving the fast charging performance of the battery, reducing battery lithium plating, and increasing the cycle life.

[0064] In some embodiments, Figure 1 As shown, a linear depression region 1 is provided on the negative electrode active material layer 3 of the negative electrode sheet, and a plurality of spaced pits 2 are provided in the linear depression region 1. The width of the linear depression region 1 is the size of the linear depression region along the width direction of the negative electrode sheet.

[0065] In the present invention, the depth of the linear depressed area is the vertical distance from the surface of the negative electrode active material layer to the bottom of the linear depressed area; the depth of the linear depressed area is less than the thickness of the negative electrode active material layer, and the linear depressed area does not penetrate the negative electrode active material layer.

[0066] In some embodiments, the linear recessed areas are arranged in a uniformly spaced arrangement, or the arrangement is adjusted according to actual needs, such as partially arranged in a uniformly spaced arrangement and partially arranged in a non-uniformly spaced arrangement.

[0067] The present invention has found that although the negative electrode silicon-carbon material can provide more lithium storage sites, during the rapid and repeated release and insertion of lithium ions, due to the complexity of the pore structure, the diffusion path of lithium ions inside the material is complex. When the battery is charged and discharged at a high rate, it is very easy to produce uneven distribution of lithium ion concentration, resulting in the formation of lithium dendrites, which will not only lead to the loss of active substances inside the battery, accelerate the decline of battery capacity, but also cause safety problems. To further solve the above problems, the present invention further proposes:

[0068] In some embodiments, the electrolyte further comprises a compound B, and the chemical formula of the compound B is shown in Formula III:

[0069] Among them, X1, X2, and X3 independently include At least one of X1, X2 and X3 contains an S group, and A1, A2 and A3 are independently selected from O, S or C-linked alkyl groups.

[0070] In the present invention, the C-linked alkyl group refers to any one of A1, A2, and A3, in which C is directly linked to the adjacent C and X (any one of X1, X2, and X3), such as formula III-9.

[0071] In the present invention, the C-linked alkyl group is an alkyl group having 1 to 3 carbon atoms, such as methyl, ethyl and propyl.

[0072] In some embodiments, based on the total mass of the electrolyte, the mass proportion of compound B is 0.1%-5%, and the mass proportion of compound B can be, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any point value in the range composed of the above two point values. Compound B is further added to the electrolyte, and the mass proportion of compound B is adjusted to meet the above range. The protective film formed by compound B on the surface of the negative electrode contains micropores or channels, which provide additional transmission paths for lithium ions, and the micropores or channels of the protective film may be connected to the openings of silicon carbon, further reducing the diffusion energy barrier and promoting the uniform deposition of lithium ions, thereby improving the fast charging and cycle life of the battery.

[0073] In some embodiments, the compound B comprises at least one of the following compounds:

[0074]

[0075] In some embodiments, compound B represented by formula III-1 is preferred.

[0076] In some embodiments, the electrolyte further includes a nitrile compound; based on the total mass of the electrolyte, the mass proportion of the nitrile compound is 0.1%-7%, and the mass proportion of the nitrile compound can be, for example, 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7% or any point value in the range composed of two points above. When the nitrile compound is added to the electrolyte and the nitrile compound is further adjusted to meet the above range, the nitrile compound has a strong oxidation resistance, which can improve the electrochemical window of the electrolyte, thereby improving the high voltage resistance of the electrolyte, reducing side reactions under high voltage, and improving the safety performance of the battery.

[0077] In the present invention, the type of the nitrile compound is not specifically limited. For example, the nitrile compound can be selected from at least one of a mononitrile additive, a dinitrile additive, and a trinitrile additive; the mononitrile additive includes but is not limited to at least one of benzonitrile, p-toluenenitrile, and 3,5-difluorobenzonitrile; the dinitrile additive includes but is not limited to at least one of adiponitrile (AND), succinonitrile (SN), and ethylene glycol bis(propionitrile) ether; the trinitrile additive includes but is not limited to at least one of 1,3,6-hexanetrinitrile (HTCN), 1,2,6-hexanetrinitrile, and 1,2,3-tris(2-cyanoethoxy)propane.

[0078] In some embodiments, the electrolyte further includes a sulfonic acid compound; based on the total mass of the electrolyte, the mass proportion of the sulfonic acid compound is 0.1%-5%, and the mass proportion of the sulfonic acid compound can be, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, or any point value in the range of the above two point values. When the sulfonic acid compound is added to the electrolyte and the sulfonic acid compound is further adjusted to meet the above range, the sulfonic acid compound can undergo a reduction reaction on the negative electrode surface during the battery charging and discharging process, especially during the first charge, to form a stable SEI film; this SEI film can inhibit the co-embedding and reduction decomposition of the solvent molecules in the electrolyte at the negative electrode, thereby reducing the generation of side reactions and improving the thermal safety performance of the battery.

[0079] In the present invention, the type of the sulfonic acid compound is not specifically limited. For example, the sulfonic acid compound can be selected from sulfonate additives; the sulfonate additives include but are not limited to 1,3-propane sultone, 1-propylene-1,3-sultone, 5-methylthiothiocyanate 2,2-dioxide, 1,3-propylene sultone, 2,4-butane sultone, 1,4-butane sultone, 1,3-butane sultone, and fluorinated 1,3-propane sultone.

[0080] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0081] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0082] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0083] Example 1-1

[0084] 1) Preparation of positive electrode

[0085] The positive electrode active materials lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), SP (super P) and carbon nanotubes (CNT) are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of an aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain the desired positive electrode sheet.

[0086] 2) Negative electrode preparation

[0087] The negative electrode active materials artificial graphite, silicon-carbon composite material, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) are mixed in a mass ratio of 74.5:20:2.5:1.5:1:0.5, deionized water is added, and the negative electrode active slurry is obtained under the action of a vacuum mixer; the negative electrode active slurry is evenly coated on the two surfaces of the negative electrode collector (tensile strength 500 MPa); the coated copper foil is dried at room temperature, and then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.

[0088] Among them, the preparation steps of the negative electrode current collector are as follows: first, a copper sulfate electrolyte is prepared, and then in the electrolytic cell of the foil machine, the copper sulfate electrolyte is subjected to the action of direct current to enable copper ions to obtain electrons and deposit on the surface of the cathode roller to form a foil (copper) with a thickness of 6 μm. After continuous rotation of the cathode roller, the copper foil is continuously peeled off, and then the copper foil is immersed in an electroplating tank containing a chromium plating solution, and a chromium protective layer with a thickness of 5 nm is plated on the surface of the copper foil through an electrochemical reaction. Subsequently, a graphite carbon layer with a thickness of 6 nm is coated on the surface of the copper foil by a spraying method to obtain a negative electrode current collector with a tensile strength of 500 MPa.

[0089] 3) Preparation of electrolyte

[0090] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), EC, PC, DEC, and PP are mixed in a mass ratio of 10:20:20:50, and then 15% of the total mass of the electrolyte is added to the formula I-2 and formula II-6 compounds (the mass of the formula I-2 and formula II-6 is 1:1) and mixed evenly. Then, 14wt% of fully dried LiPF6 based on the total mass of the electrolyte is quickly added, 10% of fluoroethylene carbonate based on the total mass of the electrolyte is added, 1% of ADN, 1.5% of SN, 2.5% of HTCN and 3% of 1,3-propane sultone based on the total mass of the electrolyte are added, and after stirring evenly, the desired electrolyte is obtained after passing the moisture and free acid tests.

[0091] 4) Preparation of batteries

[0092] The positive electrode sheet of step 1), the negative electrode sheet of step 2) and the separator are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the electrolyte of step 3) is injected into the outer packaging, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes. The battery of the present invention has a charge and discharge range of 3.0-4.53V.

[0093] 5) Test the battery

[0094] i) 25℃4C cycle test

[0095] The battery obtained in the embodiment and the comparative example was discharged to 3.0V at 0.5C at 25°C. Then it was charged at 5C constant current to 4.53V, then charged at 4.53V to 0.05C constant voltage, left to stand for 5 minutes, and then discharged at 5C constant current to 3.0V. This is one charge and discharge cycle. The discharge capacity of the first week of the test is x mAh, and the discharge capacity of the Nth week is y mAh; the capacity of the Nth week is divided by the capacity of the first week to obtain the cycle capacity retention rate R=y / x of the Nth week, and the number of battery cycles when the capacity retention rate is 80% is recorded.

[0096] ii) Hot box performance test

[0097] At room temperature, the battery obtained in the embodiment and comparative example was charged to 4.53V at 1C constant current, left to stand for 60 minutes, and the appearance was checked and photographed. Then the temperature was raised to 132℃±2℃ at a rate of 3℃ / min±2℃ / min and maintained for 60 minutes. The sample was observed, and it was recorded as passing the test if there was no leakage, no smoke, no fire, and no explosion. Ten samples were tested for each embodiment or comparative example, and the pass rate of the hot box performance test was recorded.

[0098] iii) Cyclic corner crack test

[0099] First, observe whether the four corners of the battery are cracked after the cycle test (25℃4C cycle test). If there is no obvious crack, use a 3D profilometer to scan the battery to observe whether there are cracks at the four corners of the battery's internal winding core to determine whether the battery has corner cracks. 10 samples are tested for each embodiment or comparative example, and the probability of corner cracks is recorded.

[0100] iv) Battery lithium deposition test

[0101] The battery that has been cycled (after 25°C 4C cycle test) is fully charged again (charging conditions are the same as 25°C 4C cycle), and then the battery is dissected to observe whether there is lithium deposition at the negative electrode interface. 10 samples are tested for each embodiment or comparative example, and the probability of lithium deposition is recorded.

[0102] Example 1-2 and Comparative Example 1-2 were carried out with reference to Example 1-1, and the main differences are shown in Table 1. Among them, Example 1 changed the open pore volume of the silicon-carbon material; Example 2 changed the mass proportion of compound A in the electrolyte. Comparative Example 1 was that the mass proportion of compound A in the electrolyte was too small and did not meet the formula range. Comparative Example 2 was that compound A was not introduced into the electrolyte.

[0103] Table 1

[0104]

[0105]

[0106] Note: “ / ” indicates that the corresponding parameter is not tested.

[0107] It can be seen from Table 1 that the present invention can improve the fast charging performance of the battery and increase the thermal safety performance and cycle life of the battery by adjusting the open pore volume of the silicon-carbon material and the mass proportion of compound A in the electrolyte.

[0108] Example 3 was carried out in accordance with Example 1-1, and the main differences are shown in Table 2. In Example 3, the type of compound A was changed.

[0109] Table 2

[0110]

[0111] It can be seen from Table 2 that compound A satisfying the structure of formula I can play a similar role, wherein when compound A of formula I and compound A of formula II are used in combination, the battery can have better thermal safety performance.

[0112] The examples 4-6 were carried out with reference to the examples 1-1, and the main differences are shown in Table 3. Among them, the tensile strength of the negative electrode current collector was changed in the example 4. The content of silicon in the negative electrode active material was changed in the example 5. The mass proportion of fluoroethylene carbonate (FEC) in the electrolyte was changed in the example 6.

[0113] Table 3

[0114]

[0115] Note: “ / ” indicates that the corresponding parameter is not tested.

[0116] It can be seen from Table 3 that the present invention can suppress the corner cracks caused by the expansion of the negative electrode, reduce lithium precipitation, further improve the thermal safety problem of the battery and enhance the thermal safety performance of the battery by adjusting the mass proportion of fluoroethylene carbonate in the electrolyte, the mass proportion of silicon in the negative electrode active material and the tensile strength of the negative electrode current collector.

[0117] Example 7 was carried out with reference to Example 1-1, and the main differences are shown in Table 4. In particular, on the basis of Example 1-1, Example 7 further introduced compound B into the electrolyte, and the mass proportion of compound B was changed.

[0118] Table 4

[0119]

[0120] As can be seen from Table 3, the present invention can inhibit the formation of lithium dendrites, reduce lithium precipitation, and improve the battery cycle life and thermal safety performance by further adding compound B to the electrolyte and adjusting the mass proportion of compound B in the electrolyte.

[0121] Example 8 was carried out with reference to Example 7-1, and the main differences are shown in Table 5. In particular, the type of compound B was changed in Example 8.

[0122] Table 5

[0123]

[0124] It can be seen from Table 5 that compound B satisfying the structure of formula III can play a similar role, both of which can improve the cycle life and thermal safety performance of the battery and reduce lithium plating.

[0125] Example 9 was carried out in accordance with Example 7-1, and the main differences are shown in Table 6. In Example 9, a linear depression area is further provided on the negative active material layer of the negative electrode sheet. The specific operation steps are: arc-shaped grooves are formed on the surface of the negative active layer of the obtained negative electrode sheet using a continuous laser, parallel to the width direction of the negative electrode sheet, the spacing between adjacent grooves is 2 mm, the width of the groove is 100 μm, and the depth of the groove is 15 μm.

[0126] Table 6

[0127]

[0128] It can be seen from Table 6 that the present invention can increase the contact area between the negative electrode material and the electrolyte and improve the cycle life of the battery by further arranging a linear recessed area in the negative electrode active material layer.

[0129] Example 10 was carried out with reference to Example 1-1, and the main differences are shown in Table 7. In Example 10, the mass ratio of nitrile compounds and / or sulfonic acid compounds in the electrolyte was changed, and the mass ratio of ADN, SN and HTCN was the same as that of Example 1-1.

[0130] Table 7

[0131]

[0132] Note: “ / ” indicates that the corresponding parameter is not tested.

[0133] It can be seen from Table 7 that the present invention can improve the fast charging performance of the battery and increase the thermal safety performance and cycle life of the battery by adjusting the mass proportion of nitrile compounds and sulfonic acid compounds in the electrolyte.

[0134] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0135] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector. The negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon material. The open pore volume of the silicon-carbon material is recorded as x mm 3 / g; x satisfies: 0.1≤x≤100; The electrolyte includes compound A, and the mass proportion of compound A is y% based on the total mass of the electrolyte; the chemical formula of compound A is shown in formula I and / or formula II: Formula I: Formula II: Wherein, R1, R2, R3, and R4 independently include F, Cl-substituted or unsubstituted hydrocarbon groups or hydrocarbonoxy groups having 1 to 8 carbon atoms, at least one of R1 and R2 contains F, and at least one of R3 and R4 contains F; x and y satisfy: 0.05<y / x≤120.

2. The lithium-ion battery according to claim 1, characterized in that x and y satisfy: 0.1<y / x≤100; Preferably, more preferably 1≤x≤70; Preferably, y satisfies: 5≤y≤30.

3. The lithium-ion battery according to claim 1, characterized in that The compound A shown in formula I includes at least one of the following compounds: And / or, the compound A shown in formula II includes at least one of the following compounds: Preferably, the compound A comprises a compound represented by formula I and a compound represented by formula II, and the mass ratio of the two is 1:(1-4).

4. The lithium-ion battery according to claim 1, characterized in that The tensile strength of the negative electrode current collector is denoted as σMPa; σ satisfies: 450≤σ≤750; Preferably, the thickness of the negative electrode current collector is 2 μm-10 μm.

5. The lithium-ion battery according to claim 4, characterized in that: In the negative electrode active material, the content of silicon element is recorded as m%; The electrolyte includes fluoroethylene carbonate, and the mass proportion of fluoroethylene carbonate is n% based on the total mass of the electrolyte; m, n and σ satisfy: 10<(n+σ) / m≤500; Preferably, m satisfies: 1<m≤50; and / or, n satisfies: 0.1<n≤20.

6. The lithium-ion battery according to claim 1, characterized in that The sphericity of the silicon-carbon material is 0.5-1; And / or, the Dv10 of the silicon-carbon material is 1 μm-10 μm; And / or, the silicon-carbon material is doped with element M, and element M includes at least one of K, Ca, and Na; preferably, the content of element M is 100 ppm-10000 ppm.

7. The lithium ion battery according to any one of claims 1 to 6, characterized in that: The electrolyte further comprises a compound B, and the chemical formula of the compound B is shown in Formula III: Among them, X1, X2, and X3 independently include and at least one of X1, X2, and X3 contains an S group, and A1, A2, and A3 are independently selected from O, S, or C-linked alkyl groups; Preferably, based on the total mass of the electrolyte, the mass proportion of compound B is 0.1%-5%.

8. The lithium-ion battery according to claim 7, characterized in that: The compound B comprises at least one of the following compounds:

9. The lithium ion battery according to any one of claims 1 to 6, characterized in that: A linear concave region is provided on the negative electrode active material layer, and the width of the linear concave region is 50 μm-200 μm; Preferably, the linear recessed area has a depth of 3 μm-45 μm.

10. The lithium ion battery according to any one of claims 1 to 6, characterized in that: The electrolyte further comprises a nitrile compound; based on the total mass of the electrolyte, the mass proportion of the nitrile compound is 0.1%-7%; Preferably, the electrolyte further comprises a sulfonic acid compound; based on the total mass of the electrolyte, the mass proportion of the sulfonic acid compound is 0.1%-5%.

Citation Information

Patent Citations

  • Lithium secondary battery

    CN115036572A

  • Negative active material, negative plate and lithium ion battery

    CN117936722A

  • Nano silicon-carbon composite material as well as preparation method and application thereof

    CN118173733A

  • Lithium ion secondary battery

    CN118738569A

  • Lithium-ion battery

    WO2024037187A1

Cited By

  • Lithium ion secondary battery

    CN119786701A

  • A lithium ion secondary battery

    CN119786701B

  • Lithium ion secondary battery

    US12500245B1

  • Lithium-ion battery

    WO2026098160A1